A rat arteriovenous graft model using decellularized vein. (October 2020) - Bai, Hualong; Wang, Zhiwei; Li, Mingxing; Sun, Peng; Wang, Wang; Liu, Weizhen; Wei, Shunbo; Wang, Zhiju; Xing, Ying; Dardik, Alan
Background: The high rate of clinical failure of prosthetic arteriovenous grafts continues to suggest the need for novel tissue-engineered vascular grafts. We tested the hypothesis that the decellularized rat jugular vein could be successfully used as a conduit and that it would support reendothelialization as well as adaptation to the arterial environment. Materials and methods: Autologous (control) or heterologous decellularized jugular vein (1 cm length, 1 mm diameter) was sewn between the inferior vena cava and aorta as an arteriovenous graft in Wistar rats. Rats were sacrificed on postoperative day 21 for examination. Results: All rats survived, and grafts had 100% patency in both the control and decellularized groups. Both control and decellularized jugular vein grafts showed similar rates of reendothelialization, smooth muscle cell deposition, macrophage infiltration, and cell turnover. The outflow veins distal to the grafts showed similar adaptation to the arteriovenous flow. Both CD34, CD90 and nestin positive cells, as well as M1-type and M2-type macrophages accumulated around the graft. Conclusions: This model shows that decellularized vein can be successfully used as an arteriovenous graft between the rat aorta and the inferior vena cava. Several types of cells, including progenitor cells and macrophages, are present in the host response to these grafts in this model. This model can be used to test the application of arteriovenous grafts before conducting large animal experiments.